Project approach and development of the mechanism of management of tourist destinations - M. Ahmad (Publishing House of the State University of Management, 2021)
The article makes an overview of approaches to heritage management, explains the concept of a tourist destination, as well as the importance of using a project management approach and its tools in managing a tourist heritage destination. The paper considers a group of integrated projects that invest in heritage as a factor of attractiveness of a tourist destination, since it is part of a tourism system that cannot be managed separately and is integrated for the production of a tourism product. Taking into account the importance of preserving heritage values, the project approach involves the engagement of various stakeholders in this process and the creation of a mechanism to increase the effectiveness of tourism investments for the benefit of society, business and the state.